Isolation, identification and antibiotic sensitivity pattern of Escherichia coli isolated from various clinical sample in a tertiary care hospital, Jaipur, Rajasthan, India - Das, Bitopan; Sarma, Mrinmoy; Kumar, Rohit; Borah, Palashi; Sinha, Sushama; Gupta, Prasanna; Durlabhji, Pushpa (International Journal of Research in Medical Sciences, 2020)
Background: Escherichia coli is one of the most frequent causes of many bacterial infections, including Urinary Tract Infections (UTI), blood stream infections, otitis media, pneumonia, meningitis, traveler’s diarrhoea, enteric infections and systemic infections. This study was done with the aim to surveying antibiotic sensitivity pattern of isolated Escherichia coli in both sex attended in NIMS Hospital, Jaipur under the taken time period. Methods: In this cross-sectional study, 62 Escherichia coli were isolated from various clinical specimens of the patients attending both OPD and IPD. The strains were selected using the laboratory standard methods and culture-specific. The antibiotic susceptibility testing was performed using Kirby-Bauer disk diffusion method. Results: Out of total 62 isolates of Escherichia coli 26(41.93%) isolates were from male while 36(58.064%) from female patients. Maximum sensitivity were shown by Polymyxin B and Colistin i.c 100% followed by Nitrofuratonin 82.5% followed by Meropenem 79.03%, Aztreonam 72.58%, Piperacillin/ Tazobactam and Ciprofloxacin 61.30%, each Amikacin 56.45%, Imipenem 54.83%, Ofloxacin 45.16%, Cefepime 43.54%, Ceftazidime 38.71%, Gentamycin and Ceftriaxone 37.09% each, Cefotaxime 30.64%, Norfloxacin 27.5%. Maximum resistance shown against Norfloxacin 72.5%, followed by Gentamycin and Ceftriaxone 62.90%, Ceftazidime 61.30%. Conclusions: Escherichia coli infected more in urinary tract infection as compare to other sample in human, and it is common in female than male. Regular monitoring of antimicrobial susceptibility for E.coli is recommended to improve treatment. A changing trend in antibiotic sensitivity profile of the isolates need to be monitored as there is limited availability of newer drugs and the emergence of resistant bacteria far exceeds the rate of new drug development.